3D printed honeycomb cellular beams made of composite materials (plastic and timber). (10th January 2022) - Ghanbari-Ghazijahani, Tohid; Kasebahadi, Mohammad; Hassanli, Reza; Classen, Martin
Graphical abstract: Highlights: Printability (3D) of beams of two recycled materials was evaluated experimentally. Flexural (bending) tests showed excellent performance of the composite beams. Composite beams with plastic showed higher loads than beams with timber. We quantified to what extent and which material can provide flexural strength. The infill density was found to be effective in bending capacity. Abstract: The abundance of the waste materials of wood and plastic inspired the authors to explore the possibility of 3D printing the recycled materials as composite beams. This paper addresses the design, fabrication, and structural testing of 3D printed composite beams under 3-point bending. The authors believe that 3D printing of beams from timber waste and Polylactic Acid (PLA) is a state-of-the-art and has excellent potential to be transformed to state-of-the-practice in the construction industry. Beams with different compositions of materials and printing densities were designed, printed and tested to failure. This paper elaborates details of the design and printing of the beams, which then will be followed by detailed discussions as to how each beam reacts under flexural loading in terms of deformability, stiffness, strength-to-mass ratio, failure, and load-carrying capacity. General deformations of the specimens implied that the design of the specimens was quite successful in avoiding any premature failure. Large deflections of all specimens indicated that the shear strengthening performed effectively as the shear-vulnerable areas were not affected by the shear failure. The infill density affects the flexural capacity, which is obviously due to the amount of material present against loading. The capacity of the specimens with PLA at the top and bottom sections of the beams was higher than the equivalent beams with timber flanges. Overall, very promising results were obtained with a view to extending the idea into more advanced elements and techniques to develop various 3D printed structural elements towards the ongoing discussion on automation in the construction and prefabrication.